Public and Third Sector Leadership : Experience Speaks. - Howieson, Brian (Emerald Group Publishing Limited, 2014)
What can we learn from leaders in the public and third sectors? This book is unique in that it provides an opportunity for the voices of these individuals to be heard. Each leader considers what leadership means to them, their experience of it, and the complex challenges they face as a result of profound changes in the economy, polity and society.